The Influence of Knowledge Sharing on Innovation Performance in Class I Prison, Central Jakarta - Sarah Eveline; Kusmiyanti Kusmiyanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
Knowledge sharing is an important factor for an organization in generating ideas that can be used to improve innovation performance and organizational development. However, the unevenness of shared knowledge causes innovation performance in an organization to be hampered. Therefore, it is important to share knowledge to gain experience, information and ideas to improve the innovation performance of an organization. This study aims to determine the effect of knowledge sharing on innovation performance at the Class I State Prison Central Jakarta. This study uses a quantitative survey design method with sample withdrawal using simple probability sampling technique. The sample used in this study amounted to 155 employees at the Class I State Prison Central Jakarta. The data collection method uses a questionnaire distributed via google form. This questionnaire contains 12 statement items related to the variables studied. Data analysis techniques are carried out through the outer model and inner model, namely validity test, reliability test, r square, goodness of fit, f square, and path coefficients which are processed using SmartPLS software. The results of the outer loading, AVE, HTMT, Cronbach's alpha, and composite reliability research are declared valid and reliable. The r square test results obtained a value of 0.579 which explained that the effect of knowledge-sharing variables on innovation performance of 57.9% was stated to be moderate and the remaining 42.1% was influenced by other variables not explained in this study. From the results of this study, it can be concluded that there is an effect of knowledge sharing on innovation performance at the Class I State Prison in Central Jakarta.